2007
DOI: 10.1128/jcm.00465-07
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study To Evaluate Bloodstream Infection by Helicobacter cinaedi in Japan

Abstract: Helicobacter cinaedi has being recognized as an important human pathogen which causes bloodstream infections. Although the first case of bacteremia with this pathogen in Japan was reported in 2003, the true prevalence of H. cinaedi as a pathogen of bloodstream infections in this country is not yet known. Therefore, the aim of our study was to assess the incidence of bacteremia with H. cinaedi in Japan. We conducted a prospective, multicenter analysis in 13 hospitals during 6 months in Tokyo, Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
85
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 17 publications
0
85
1
Order By: Relevance
“…It has been suggested that H. cinaedi is part of the normal intestinal flora in rodents, which might be a reservoir for human infections (8,10). There are also several papers reporting that direct contact with pets may be a possible route of infection in humans (3,4,13,44); however, details regarding the pathogenesis and epidemiological features, including routes of infections of animal isolates in the context of humans and animals, are not fully understood. Among the animal strains examined in this study, only strain 94105 was isolated from a diseased animal (a 2-month-old female puppy with bloody diarrhea) (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that H. cinaedi is part of the normal intestinal flora in rodents, which might be a reservoir for human infections (8,10). There are also several papers reporting that direct contact with pets may be a possible route of infection in humans (3,4,13,44); however, details regarding the pathogenesis and epidemiological features, including routes of infections of animal isolates in the context of humans and animals, are not fully understood. Among the animal strains examined in this study, only strain 94105 was isolated from a diseased animal (a 2-month-old female puppy with bloody diarrhea) (26).…”
Section: Discussionmentioning
confidence: 99%
“…This microorganism was first isolated from homosexual men as a Campylobacter-like organism (CLO) and was initially recognized as a rectal and intestinal pathogen among members of this population (1). However, H. cinaedi is now considered to be an opportunistic pathogen that causes bacteremia, cellulitis, septicemia, and enteritis in immunocompromised patients (2)(3)(4), immunocompetent patients, and even healthy individuals (5)(6)(7).…”
mentioning
confidence: 99%
“…Although Helicobacter species are recognized as major pathogens associated with gastrointestinal tract infection, H. cinaedi is commonly isolated from compromised patients. [6][7][8]10) However, there have been increasing reports of infection in immunocompetent patients in whom H. cinaedi has been isolated from blood and caused recurrent bacteremia and latent or chronic infections. [6][7][8]10) Recently Lewis, et al 9) reported isolation of H. cinaedi from an immunocompetent patient with myopericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Helicobacter cinaedi is commonly isolated from compromised patients; however, there are increasing reports of this organism infecting immunocompetent patients. [6][7][8] H. cinaedi infection is reportedly associated with cardiovascular disease. 9,10) We here report a case of a pericoronary pseudotumor caused by H. cinaedi.…”
mentioning
confidence: 99%
“…Later in 1991, on the basis of hybridization data, this organism was reclassified as belonging to the genus Helicobacter (2). Although H. cinaedi infections previously were reported mainly in immunocompromised patients (3)(4)(5)(6)(7), recently increasing numbers of infection have been reported in immunocompetent patients (8,9). Examples of the diverse range of infections caused by H. cinaedi include proctocolitis, gastroenteritis, neonatal meningitis, localized pain, rash and bacteremia (10).…”
mentioning
confidence: 99%